Investigation into expansion of illegal construction in the National Park of Curonian Spit - Šostak, Olga Regina; Kutut, Vladislavas (Business: Theory and Practice, 2009)
The World Heritage List includes the Curonian Spit as a valuable cultural landscape – a unique harmony between the nature and human activities, a harmony that emerged through centuries. The Curonian Spit retains its cultural landscape, which is still evolving and keeps an active social part in the modern society through its traditions. it was ecological wisdom, enormous physical efforts and financial input of people that enabled, in the 19th century, creation of a cultural landscape which later was managed and maintained with care. The problem of preservation and continuation of landscaping traditions, of their transfer to future generations, gained the momentum recently, after the notorious boom of unsanctioned building work in the National Park of the Curonian Spit and other territories marked as cultural landscape. in order to protect the public interest in the National Park of the Curonian Spit, Klaipėda County and the Prosecutor’s office of Klaipėda brought over 30 civil lawsuits and claims on alleged infringements related to expanding constructions in the National Park of the Curonian Spit. The current situation in the area of unauthorised building is not satisfactory. Unauthorised building is quite frequent in Lithuania. Builders commence building work which violates laws for various reasons: the complex procedures related to issuing of building permits, assumptions leading to hopes that it will be possible to legalise their unauthorised buildings and/or constructions, as well as the national mentality—attempts to “drive through” laws instead of following them, etc. As illustrated by practical examples, the process of unauthorised building does not pose difficulties (control of this process is underdeveloped and includes numerous “compromises”). Generally, persons involved in unauthorised building work encounter real problems only during the last stage, which is related to execution of their rights to the built object. The legislation which currently regulates procedures related to detection, stopping and relief of the effects of unauthorised building foresees demolition of any unauthorised building and construction; but builders search for possibilities to legalise such buildings and constructions nevertheless. This article analyses the concept of illegal building work and the liabilities for illegal building.Article in Lithuanian.Neteisėtos statybų plėtros tyrimas Kuršių nerijos nacionaliniame parkeSantrauka. Kuršių nerijos nacionalinis parkas įsteigtas siekiant išsaugoti savitą kultūros paveldą, iškelti iš jo objektus teršiančius aplinką, propaguoti Kuršių nerijos gamtos ir kultūros vertybes ir užtikrinti jų apsaugą. Valstybė, priimdama teisės aktus, kuriais nustatytas specialus Kuršių nerijos nacionalinio parko teisinis režimas, siekė išsaugoti unikalų gamtos ir žmogaus sukurtą kraštovaizdžio kompleksą Lietuvos ir Europos saugomų gamtos ir kultūros paveldo vertybių sistemoje. Kuršių nerijos gamtos ir kultūros vertybių išsaugojimo, tęstinumo ir perdavimo ateities kartoms problema ypač aktuali tapo pastaruoju metu, kai didelį rezonansą sukėlė savavališkų statybų bumas Kuršių nerijos nacionaliniame parke ir kitose kultūrinio kraštovaizdžio teritorijose, kai  buvo  suabejota  Kuršių  nerijos  nacionalinio  parko  planavimo  schemos  galiojimu.  Gindami  viešąjį  interesą  Kuršių  nerijos nacionaliniame parke Klaipėdos apygardos ir Klaipėdos miesto prokuratūros teismams yra pateikusios per 30 civilinių ieškinių bei prašymų dėl galimų teisės aktų pažeidimų, susijusių su statybų plėtra Kuršių nerijos nacionaliniame parke. Tam, kad Kuršių nerijos nacionalinio parko teritorijoje nebūtų vykdoma bet kokio pobūdžio veikla, išskirtinai statybinė, nesilaikant šiai terito-rijai teisės aktais nustatyto specialaus priežiūros bei naudojimo režimo, straipsnyje atliktas savavališkų statybų Kuršių nerijos nacionaliniame parke atsiradimo priežasčių tyrimas, atskleista savavališkų statybų samprata. Dabartinė padėtis neteisėtų statybų srityje nėra patenkinama. Neteisėtos statybos mūsų šalyje – neretas atvejis. Statytojai gali statyti pažeisdami įstatymus dėl įvairių priežasčių. Šiuo metu savavališkų statybų išaiškinimo, sustabdymo, padarinių šalinimo tvarką reglamentuoja tokie teisės aktai, kurie eliminuoja galimybę savavališkas statybas įteisinti ir numato savavališkai pastatytų statinių nugriovimą.Reikšminiai žodžiai: statybų plėtra Kuršių nerijos nacionaliniame parke, kultūrinio kraštovaizdžio vertybių išsaugojimas, Kuršių nerijos nacionalinio parko schema (generalinis planas), teisinis savavališkų statybų reglamentavimas.First published online: 22 Sep 2009